Does sense of work gain predict team creativity? The mediating effect of leader-member exchange and the moderating effect of work smoothness - Shi, Kun; Zhang, Zhifan; Zhang, Hua (Frontiers in Psychology, 2023)
The present study examines the link between the sense of work gain and team creativity and explore the mediating and moderating roles of Leader-member exchange (LMX) and work smoothness on this link. The results based on 484 valid samples from an online survey of a human resources company，reveal that the sense of work gain can positively predict team creativity, and LMX mediate the associations of sense of work gain and team creativity. Moreover, work smoothness emerged as a significant moderator can moderate the associations between sense of work gain and team creativity, as well as moderating the relationship between LMX and team creativity.